2015
DOI: 10.1007/s12663-014-0737-2
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Stafne Bone Cyst

Abstract: Stafne bone cyst is a rare mandibular defect. It is a developmental abnormality that commonly presents as a small, well demarcated, and asymptomatic radiolucency seen at the angle of the mandible below the mandibular canal. There are usually no clinical signs nor symptoms. Diagnosis is commonly by plain X-ray, but use of more accurate imaging such as MRI is required in atypical cases. This case study reports an unusual presentation of Stafne bone cyst in the ramus of the mandible in a young man and reviews the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 15 publications
2
20
0
5
Order By: Relevance
“…In the present report, these imaging features are present and depression limits are defined by a thin sclerotic discontinuous border. The LMBD is continuous to mandible base, as also demonstrated in a previous report [19], which mandible base similarly presents discontinuity of its cortical bone. However, in literature, we also found reports with thick LMBD margins, continuous to the mandible base, without any cortical interruption [20,21].…”
Section: Discussionsupporting
confidence: 84%
“…In the present report, these imaging features are present and depression limits are defined by a thin sclerotic discontinuous border. The LMBD is continuous to mandible base, as also demonstrated in a previous report [19], which mandible base similarly presents discontinuity of its cortical bone. However, in literature, we also found reports with thick LMBD margins, continuous to the mandible base, without any cortical interruption [20,21].…”
Section: Discussionsupporting
confidence: 84%
“…10 The case presented by Mann and Shields 10 was an archeological sample from their study of 6700 excavated dry mandibles. Lee et al 11 reported a case in Australia, in which the patient had mild hemifacial macrosomia type I, a hypoplastic right mandible and TMJ. Incidentally, his parotid salivary gland was enlarged (hypertrophic) and observed to be occupying part of the right ascending ramus.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by multidetector CT and magnetic resonance imaging (MRI), as well as ultrasound-guided needle biopsy of the parotid tissue. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Although the most common location is the medial surface of the posterior mandible in the region of the submandibular gland fossa, 1,3,4 Philipsen et al (2002) English world medical and dental literature. [9][10][11][12][13][14][15][16][17][18][19] In a study by Sisman et al 3 Author Disclosure: None Declared.…”
Section: Introductionmentioning
confidence: 99%